Exploring the implications of social inequalities in community forestry: emerging lessons from two forests in Indonesia. (2015) - Race, Digby; Sumirat, Bugi
Community forestry has been developed internationally as a policy response to reduce deforestation and to improve the livelihoods of forest-dependent communities. This article discusses the social dimension of community forestry, and uses the concept of social capital to analyse the implications of social inequalities in two community forestry initiatives in Indonesia. The article concludes with some revealing insights about the: 1) temporal nature of social capital in community forestry; 2) ways social capital can entrench inequalities; 3) role of 'outsiders' assisting the development of community forestry.